Addiction Services for Older Adults: A Service Provider Perspective - Merla, Cristina (My University, 2013)
Substance abuse is a major public health concern. Scholars predict a growing proportion of people aged 50 years and older suffering from addiction to alcohol, prescription or over-the-counter medications and/or illegal substances (Wu & Blazer, 2011; Han et al., 2009). Available Canadian statistics reveal that 6-10% of older adults experience alcohol problems, 1% use illegal substances and approximately 6% seek addiction treatment for prescription opioids (Public Health Agency of Canada, 2010; Tjepkema, 2004; CAMH, 2008). Older adults face personal, social, and structural barriers to treatment, which result in a significant number of people living with addiction and remaining undiagnosed and untreated in the community (Crome & Bloor, 2005b). Nevertheless, this issue is significantly understudied and under-recognized, particularly within Canadian literature.
This qualitative research study examined the perspectives of addiction service providers regarding the issue of addiction among older adults. A descriptive, qualitative research design was used to explore the perspectives of addiction service providers using in-depth, semi-structured personal interviews. Purposive sampling techniques were used to recruit 24 service providers employed by Hamilton addiction services. Semi-structured interviews included questions on (a) the current provision of addiction services for older adults, (b) characteristics of older adults (c) perceived barriers to treatment, and (d) recommendations for addressing the needs of older adults living with addiction. The interview also collected demographic information to describe the demographic profile of agencies and research participants involved in the study.
By using Braun and Clarke’s (2006) phases of thematic analysis, this study observed several key themes that confirmed and extended existing literature. New contributions highlight the following: (1) according to service providers, older adults demonstrate a greater readiness for change and stronger commitment to their treatment plan regardless of whether they are enrolled in a mixed-age or age-specific program. (2) Some older adults use substances to cope with cumulative shame that stems from unresolved, traumatic early-life experiences. This new finding supports principles of the life course perspective by highlighting the impact of early life events on late life experiences. (3) Service providers can address some of the age-specific needs of older adults by assigning them to an older counselor in treatment. (4) In order to enhance treatment outcomes, older adults should direct their care and be viewed as experts in their treatment needs. (5) From the perspective of service providers, older and younger adults benefit from interactions with each other when the older adult is in recovery and the younger adult is recovering. Older adults recovering also benefit from interactions with older peers in recovery, particularly when they are in mixed-age programs. Opportunities for peer interaction during and after treatment can produce favourable recovery outcomes.
Keywords: seniors; substance abuse; drug abuse; age-specific; treatment; addiction; Other Mental and Social Health; Social Work; Substance Abuse and Addiction; Other Mental and Social Health